Cultural values of Hung Kings worship in Vietnam - Loi, Le Van (Linguistics and Culture Review, 2021)
The worship of Hung Kings is a unique type of beliefs that takes an important role in the spiritual and emotional life of many Vietnamese generations. This type of beliefs has existed since ancient times and has become one of the factors that create an exceptional and influential culture of the Vietnamese people. This article studies the history of formation and development of Hung Kings worship and cultural values of Hung Kings worship to understand the spiritual meaning, sense of origin, moral traditions of this beliefs in the spiritual life of Vietnam.